The Cognition of Severe Moral Failure: A Novel Approach to the Perception of Evil - Govrin, Aner (Frontiers in Psychology, 2018)
Throughout its history moral psychology has paid little attention to the subject of evil. Here I describe the perception of evil as a categorization judgment, based on a prototype, with extensive feedback loops and top-down constraints. Based on the attachment approach to moral judgment (Govrin, 2014), I suggest that the perception of evil consists four salient features: extreme asymmetry between victim and perpetrator; a specific perceived attitude of the perpetrator towards the victim's vulnerability; the observer’s inability to take the perpetrator’s perspective, and insuperable differences between the observer and perpetrator’s judgment following the incident. In the third part of this chapter, I show that the perception of evil involves a cognitive bias. The observer is almost always mistaken in his attributions of a certain state of mind to the perpetrator. The philosophical and evolutionary significance of this bias is discussed in the final part of the chapter.